Solvability of nonlinear Dirichlet problem for a class of degenerate elliptic equations - Albo Carlos Cavalheiro (Abstract and Applied Analysis)
We prove an existence result for solution to a class of nonlinear degenerate elliptic equation associated with a class of partial differential operators of the form Lu(x)=∑i,j=1nDj(aij(x)Diu(x)), with Dj=∂/∂xj, where aij:Ω→ℝ are functionssatisfying suitable hypotheses.